2007
DOI: 10.1227/01.neu.0000249194.76527.28
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Blood Flow in Traumatic Contusions Is Predominantly Reducedafter an Induced Acute Elevation of Cerebral Perfusion Pressure

Abstract: Our findings suggest that CPP elevation induced by norepinephrine is effective in improving contusional rCBF only in selected cases, which are represented by a subset of contusions with critical perfusion, which can be identified by rCBF measurements. Conversely, in contusions with rCBF higher than critical low values, the CPP elevation could probably induce a temporary breakdown of the blood brain barrier, and the norepinephrine leads to a vasoconstriction with a worsening of regional perfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 30 publications
2
20
1
Order By: Relevance
“…The basis for a paradoxical response is uncertain, but could be due to elevated intracranial pressure (ICP), hemodynamic consequences of heart failure, or autonomic dysfunction. Similar paradoxical responses have been previously reported in traumatic brain injury [76]. Close examination of a recent work that used NIRS to monitor blood oxygen saturation during postural changes in acute stroke patients reveal a paradoxical response and large intra-subject variability in line with our results [30].…”
Section: Discussionsupporting
confidence: 92%
“…The basis for a paradoxical response is uncertain, but could be due to elevated intracranial pressure (ICP), hemodynamic consequences of heart failure, or autonomic dysfunction. Similar paradoxical responses have been previously reported in traumatic brain injury [76]. Close examination of a recent work that used NIRS to monitor blood oxygen saturation during postural changes in acute stroke patients reveal a paradoxical response and large intra-subject variability in line with our results [30].…”
Section: Discussionsupporting
confidence: 92%
“…Regarding focal hypoperfusion, however, clinical studies by means of PET have shown only minor improvements in rCBF in intralesional edematous area following CPP elevation [123]. In a subsequent study [57], we showed that only intraparenchymal lesions with low critical rCBF within the intralesional edematous area can gain a minor improvement (Fig. 47).…”
Section: Fig (45)mentioning
confidence: 66%
“…These variables are normally used to evaluate meaningful responses to therapies. To our knowledge, only four kinds of tests have been applied by means of Xe-CT in TBI patients: induced hypocapnia [53][54][55], indomethacin bolus [56], norephinephrine-induced CPP elevation [57] and increase in FiO 2 from 0.35 to 0.6 [6].…”
Section: When Why and How An Xe-ct Study Should Be Performed?mentioning
confidence: 99%
“…This suggests that if one is considering placing a patient on vasopresor agents to maintain a certain CPP, it is important to know whether that patient even requires a potentially harmful drug. Furthermore, it has been shown, both in trauma [43] and in subarachnoid hemorrhage [44], that a paradoxical decrease in CBF can occur in some patients on vasoactive drugs, emphasizing the importance of measuring the individual tissue response to an intervention.…”
Section: Xenon/ct In Traumatic Brain Injurymentioning
confidence: 99%
“…Xenon/CT data shows that the pericontusional tissue around hematomas may have marginal perfusion, but are usually not truly ischemic, arguing that decompression of the ischemic hematoma with attention to preservation of surrounding tissue is the most rational approach to these lesions when surgery is indicated [43,[48][49][50]. The most appropriate medical therapy (particularly blood pressure/CPP) to ensure adequate CBF to the pericontusional tissue may also be assessed in this manner [43,50].…”
Section: Xenon/ct In Traumatic Brain Injurymentioning
confidence: 99%